Enzymatic Hydrolysis Of Soy Okara And Fermentation Using Lactobacillus Sp. To Improve Its Nutritional And Functional Benefits As Functional Food Ingredient - Lim, Siew Khim (2021)
Okara is a major industrial-waste, generated as a by-product from the soymilk manufacturer. Since okara has a high nutritional value, reusing it as a substrate for fermentation is an economical and environmentally friendly option. Lactic acid bacteria fermentation is being used to improve the aromatic fraction, by reducing hexanal, which is responsible for off-flavour and increase ketones with fruity and buttery notes in fermented food. The first stage of this study was aimed to optimize the pre-treatment of soy okara on the extraction of reducing sugars by applying a multi-enzyme complex, Viscozyme.